Case Report: Aumolertinib as Neoadjuvant Therapy for Patients With Unresectable Stage III Non-Small Cell Lung Cancer With Activated EGFR Mutation: Case Series - Feng, Shao; Qiang, Zhang; Wanwan, Cheng; Zhaozhun, Zeng; Yuewu, Xie; Shencun, Fang (Frontiers in Oncology, 2022)
Background There is no standard treatment for stage III lung cancer due to its low surgical resection rate, and improving PFS and survival of patients with III NSCLC has become an urgent challenge in clinical treatment. For EGFR mutation-positive patients, targeted therapy has the remarkable feature of high efficiency and low toxicity compared with first-line standard chemotherapy, and targeted neoadjuvant therapy needs to be further explored. Method We report 3 diagnosed cases of locally advanced unresectable NSCLC with EGFR-sensitive mutations who first received 1–2 cycles of preoperative chemotherapy neoadjuvant therapy and were treated with 110 mg daily of 3rd-generation EGFR-TKI aumolertinib instead because of poor efficacy or safety intolerance. Result After 2 cycles of aumolertinib treatment, all 3 patients achieved symptomatic remission and significant tumor size reduction and achieved downstaging to allow surgical treatment. No additional operative difficulties were added during the surgery. They continued to receive adjuvant therapy with the original dose of aumolertinib after surgical treatment, and no evidence of tumor recurrence was found until the most recent imaging examination. In addition, the course of neoadjuvant and adjuvant therapy was free of serious adverse effects. Conclusion Perioperative treatment of these three cases of locally advanced unresectable NSCLC with EGFR-sensitive mutations with the third-generation EGFR-TKI aumolertinib showed significant efficacy and excellent safety and may be a new option for targeted therapy in the perioperative period.